2006
DOI: 10.1124/mol.106.027169
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of In Vivo Nuclear Factor-κB Activation during Liver Inflammation in Mice: Prevention by Catalase Delivery

Abstract: Nuclear factor-B (NF-B) is a transcription factor that plays crucial roles in inflammation, immunity, cell proliferation, and apoptosis. Until now, there have been few studies of NF-B activation in whole animals because of experimental difficulties. Here, we show that mice receiving a simple injection of plasmid vectors can be used to examine NF-B activation in the liver. Two plasmid vectors, pNF-B-Luc (firefly luciferase gene) and pRL-SV40 (Renilla reniformis luciferase gene), were injected into the tail vein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…The major limitation of this study is that the underlying molecular mechanisms of TAA-induced up-regulation of UGTs have not been addressed. TAA-induced liver injury was typically characterized with oxidative stress and lipid peroxidation (Low et al, 2004;Natarajan et al, 2006;Aller et al, 2008), and the antioxidant treatment was very effective in preventing TAA-induced liver injury (Hyoudou et al, 2007;Tsai et al, 2010). In addition, we found in the study presented here that SLE and DDB, both proven as good antioxidants, could significantly attenuate TAA-induced liver injury and transcriptional up-regulation of UGTs.…”
Section: Discussionsupporting
confidence: 55%
“…The major limitation of this study is that the underlying molecular mechanisms of TAA-induced up-regulation of UGTs have not been addressed. TAA-induced liver injury was typically characterized with oxidative stress and lipid peroxidation (Low et al, 2004;Natarajan et al, 2006;Aller et al, 2008), and the antioxidant treatment was very effective in preventing TAA-induced liver injury (Hyoudou et al, 2007;Tsai et al, 2010). In addition, we found in the study presented here that SLE and DDB, both proven as good antioxidants, could significantly attenuate TAA-induced liver injury and transcriptional up-regulation of UGTs.…”
Section: Discussionsupporting
confidence: 55%
“…(14,15) NF-κB activity in mouse liver was easily and quantitatively measured in this system, and we demonstrated that NF-κB in liver cells is activated when the liver suffers from thioacetamide-induced injury. (16) Luciferase-based evaluation of NF-κB activity has advantages over conventional EMSA. First, the activity can be measured in live animals, so that the changes of the activity can be traced in individual animals.…”
mentioning
confidence: 99%
“…When plasmid vectors are selectively introduced to a specific type of cell, it is possible to examine the changes in NF-κB activity in those cells. Thus, the elucidation of NF-κB activity in liver cells and tumor cells during hepatic metastasis can help identify new targets for inhibition of tumor metastasis.In the present study, the mouse model developed in our previous study (16) was used to evaluate the changes in NF-κB activity in liver cells when tumor cells enter the hepatic circulation. Murine adenocarcinoma colon26 cells were selected as tumor cells, which were inoculated into the portal vein of synergetic BALB/c mice.…”
mentioning
confidence: 99%
“…A wide range of proinflammatory mediators can promote NF-κB in HSC/HMF including LPS, TNF-α, IL-1β, angiotensin II and CD40L (Seki et al, 2007). Also, NF-κB can be activated by the generation of ROS in the liver (Hyoudou et al, 2007). The induction of NFκB in association with the activation of HSC often relates to liver damage because it imposes a constraint on HSC apoptosis, further leading to aggregating hepatic fibrosis (Czechowska et al, 2015).…”
Section: Histological Findingsmentioning
confidence: 99%